2022
DOI: 10.3389/fmars.2022.892797
|View full text |Cite
|
Sign up to set email alerts
|

Response Process of Coastal Hypoxia to a Passing Typhoon in the East China Sea

Abstract: Details of the development of coastal hypoxia in response to the passage of Typhoon Bavi (2020) in the East China Sea were reconstructed by numerical modeling using a three-dimensional coupled physical–biogeochemical model. The model was validated via repeated surveys along a transect across a submerged river valley off the Changjiang Estuary before and after the passage of Typhoon Bavi. Before Bavi’s arrival, survey data indicated that the coastal hypoxia had formed off the Changjiang Estuary. However, the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Nevertheless, the capacity for storms to transport fresh OM and nutrients into a system can trigger longer-term changes to dissolved oxygen levels. Following the initial increase of oxygen from wave mixing, local biogeochemistry may be stimulated by the storm-induced arrival of fresh OM 11 , 20 , 25 leading to reductions in dissolved oxygen 21 , 26 , 27 . Coastal areas with high anthropogenic influence are particularly vulnerable to storm-induced hypoxia after an initial spike in primary production 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the capacity for storms to transport fresh OM and nutrients into a system can trigger longer-term changes to dissolved oxygen levels. Following the initial increase of oxygen from wave mixing, local biogeochemistry may be stimulated by the storm-induced arrival of fresh OM 11 , 20 , 25 leading to reductions in dissolved oxygen 21 , 26 , 27 . Coastal areas with high anthropogenic influence are particularly vulnerable to storm-induced hypoxia after an initial spike in primary production 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Particle transport and vertical mixing driven by storm-induced currents can stimulate biogeochemical cycling in the water column after receiving an influx of OM and nutrients 11 , 20 , 24 , 25 . Oxygen-consuming OM mineralization has been documented to be a prominent biogeochemical process taking place in the water column after storm disturbance 11 , 21 , 26 , 27 , although, storms have also been linked with reduced sedimentary OM and lower fluxes of dissolved inorganic carbon from the seafloor 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in recent years, despite the dangerous and challenging of field observations before and after typhoons, some field observations have been conducted to explore the characteristics and mechanisms of decomposition. Recent studies based on field observations of typhoons have reported that typhoon processes cause strong decomposition of OM in coastal areas (Lao, Chen, et al., 2023; Meng et al., 2022; Wang et al., 2017; Zhou et al., 2021). In the Yangtze Estuary, a large amount of terrestrial OM is imported into the coastal area due to the significant rainfall during typhoons, resulting in decomposition of OM and expansion of the anoxic area (Meng et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies based on field observations of typhoons have reported that typhoon processes cause strong decomposition of OM in coastal areas (Lao, Chen, et al., 2023; Meng et al., 2022; Wang et al., 2017; Zhou et al., 2021). In the Yangtze Estuary, a large amount of terrestrial OM is imported into the coastal area due to the significant rainfall during typhoons, resulting in decomposition of OM and expansion of the anoxic area (Meng et al., 2022). In addition, field observations from our previous studies have found that regardless of whether phytoplankton blooms occur after a typhoon, the enhanced water mixing caused by the typhoon leads to an increase decomposition of OM, resulting in intense oxygen depletion in the water column (Lao, Chen, et al., 2023; Lu et al., 2022; Zhou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in the coastal waters, typhoons can increase the input of massive terrestrial nutrients, and can enhance water mixing to carry the deeper eutrophic water to the upper layer (Lao et al, 2023b;2023c;Chen et al, 2024). These processes will lead to a series of marine ecological problems, such as algal blooms (Wang et al, 2016;Jiang et al, 2022;Li et al, 2022), decomposition of organic matter (Zhou et al, 2021;Lu et al, 2022;Lao et al, 2023a), hypoxia (Wang et al, 2017;Li et al, 2019;Zhao et al, 2021;Meng et al, 2022). Therefore, studying the changes in ocean hydrodynamic processes and nutrient supplies caused by typhoons will be beneficial for us in gaining a deeper understanding of their impact on the marine eco-environment.…”
Section: Introductionmentioning
confidence: 99%